'Resettlement with Chinese characteristics': the distinctive political-economic context, (in)voluntary urbanites, and three types of mismatch. Issue 3 (2nd September 2021) - Yang, Chen; Qian, Zhu
ABSTRACT: In recent years, urban resettlement as a specific form of urbanisation has gained its momentum in planning practices to accommodate newcomers of cities, in line with the macro policy reforms of urban-rural integration. This paper synthesises literature related to the proposed term 'urban resettlement with Chinese characteristics' to shed light on the distinctive and unparalleled socio-economic and spatial transformation entailed by the ongoing urban resettlement in China. Mindful of China's socialist ideology and authoritarian regime, we argue that urban resettlement has become a potent tool for the Chinese government to fuel economic development and urbanisation. The longstanding issues such as involuntary resettlement have been alleviated with the gradualist institutional changes, but emerging predicaments concerning social mismatch, space mismatch, and spatial mismatch still linger. This paper calls for researchers to draw lessons and implications from the discourse of 'urban resettlement with Chinese characteristics' to expand the knowledge of sustainable urban-rural development.